Building trust in media content: An analysis - K. C., Durga Lal (Nepali Media: Issue of Ethics and Sustainability, 2025)
In recent years, there has been a significant shift in the way audiences consume news, with a growing reliance on social media platforms and digital outlets. Social media not only disseminates news but also shapes public discourse, often bypassing traditional journalistic standards. In response, mainstream media organizations have increasingly transitioned from traditional formats to digital platforms to remain relevant and accessible. However, despite this transformation, mainstream media faces growing challenges from social media outlets, many of which do not adhere to established journalistic ethics and values. This shift has raised serious concerns about the reliability and trustworthiness of news content. The widespread influence of social media has led to the rapid spread of fake news, misinformation, disinformation, and hate speech, undermining public trust in both social and traditional media. Additionally, some mainstream media outlets have altered their reporting in reaction to social media pressure, further complicating the public’s ability to access credible information. This study explores the comparative trust levels between mainstream media and social media among audiences. Findings indicate that a majority of audiences not only obtain news from social media but also place substantial trust in it, regardless of content credibility. The study concludes that in order to ensure the dissemination of accurate and ethical news, social media platforms must be effectively monitored, regulated, and held to journalistic standards.